How advanced technological approaches are reshaping sustainable social media crisis management and communication: a systematic review - Bukar, Umar Ali; Sidi, Fatimah; A. Jabar, Marzanah; Nor, Rozi Nor Haizan; Abdullah, Salfarina; Ishak, Iskandar; Alabadla, Mustafa; Alkhalifah, Ali (Multidisciplinary Digital Publishing Institute, 2022)
The end goal of technological advancement used in crisis response and recovery is to prevent, reduce or mitigate the impact of a crisis, thereby enhancing sustainable recovery. Advanced technological approaches such as social media, machine learning (ML), social network analysis (SNA), and big data are vital to a sustainable crisis management decisions and communication. This study selects 28 articles via a systematic process that focuses on ML, SNA, and related technological tools to understand how these tools are shaping crisis management and decision making. The analysis shows the significance of these tools in advancing sustainable crisis management to support decision making, information management, communication, collaboration and cooperation, location-based services, community resilience, situational awareness, and social position. Moreover, the findings noted that managing diverse outreach information and communication is increasingly essential. In addition, the study indicates why big data and language, cross-platform support, and dataset lacking are emerging concerns for sustainable crisis management. Finally, the study contributes to how advanced technological solutions effectively affect crisis response, communication, decision making, and overall crisis management.